Malaria, Intestinal Helminths and Other Risk Factors for Stillbirth in Ghana - Nelly J. Yatich; Ellen Funkhouser; John E. Ehiri; Tsiri Agbenyega; Jonathan K. Stiles; Julian C. Rayner; Archer Turpin; William O. Ellis; Yi Jiang; Jonathan H. Williams; Evans Afriyie-Gwayu; Timothy Phillips; et al. (Hindawi Limited, 2010)
Objective. The objective of the study was to assess Plasmodium/intestinal helminth infection in pregnancy and other risk factors for stillbirth in Ghana. Methods. A cross-sectional study of women presenting for delivery in two hospitals was conducted during November-December 2006. Data collected included sociodemographic information, medical and obstetric histories, and anthropometric measures. Laboratory investigations for the presence of Plasmodium falciparum and intestinal helminths, and tests for hemoglobin levels were also performed. Results. The stillbirth rate was relatively high in this population (5%). Most of the stillbirths were fresh and 24% were macerated. When compared to women with no malaria, women with malaria had increased risk of stillbirth (OR=1.9, 95% CI=1.2-9.3). Other factors associated with stillbirth were severe anemia, low serum folate concentration, past induced abortion, and history of stillbirth. Conclusion. The fact that most of the stillbirths were fresh suggests that higher quality intrapartum care could reduce stillbirth rates.